2021
DOI: 10.18502/ijph.v50i3.5601
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Factors-Based Nursing Case Management Could Effectively Reduce the Incidence of Pressure Sores in Hospitalized Patients

Abstract: Background: To explore the effects of risk factors-based nursing management on the occurrence of pressure sores in hospitalized patients. Methods: From Jan 2018 to Jun 2018, 289 hospitalized patients were divided into pressure sores group [100] and control group [189] for retrospective analysis. Overall, 260 hospitalized patients from Jun 2018 to Dec 2018 were followed up for nursing intervention. Overall 130 patients received risk factors-based nursing case management were in the intervention group, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
1
3
Order By: Relevance
“…This result was slightly greater than that of studies conducted in Australia, which reported a prevalence of 2.6% [38], in China, which reported a prevalence of 1.6% [39], and in Wolaita, which reported a prevalence of 3.4% [40]. The possible reasons for these discrepancies might explain the greater prevalence in this study, which may be linked to the small sample size of the studies in Wolaita; the nding from Australia was based on a prospective cohort study design; and the diversity of the study participants' cultures, the difference in quality of care provided, and good feeding habits in China.…”
Section: Discussioncontrasting
confidence: 68%
“…This result was slightly greater than that of studies conducted in Australia, which reported a prevalence of 2.6% [38], in China, which reported a prevalence of 1.6% [39], and in Wolaita, which reported a prevalence of 3.4% [40]. The possible reasons for these discrepancies might explain the greater prevalence in this study, which may be linked to the small sample size of the studies in Wolaita; the nding from Australia was based on a prospective cohort study design; and the diversity of the study participants' cultures, the difference in quality of care provided, and good feeding habits in China.…”
Section: Discussioncontrasting
confidence: 68%
“…This might be attributable to differences in characteristics of patients, disease conditions of patients, difference in hospital factors such as nursing care service,awareness, training to secondary conditions of patients, and the fact that the previous study included all the wards. This result was slightly higher than studies conducted in Australia, with a prevalence of 2.6% [38],in China, with a prevalence of 1.6% [39],and Wolaita, with a prevalence of 3.4% [40]. The possible reasons for the discrepancies might explain the higher prevalence in this study, may be linked to the small sample size of the studies in Wolaita; the nding from Australia was based on a prospective cohort study design; and the diversity of the study participants' cultures, the difference in quality of care provided,and good feeding habits in China.Additionally, the variations can be related to instruction and adherence to procedures for pressure ulcer prevention techniques.…”
Section: Discussioncontrasting
confidence: 66%
“…This result was slightly higher than studies conducted in Australia, with a prevalence of 2.6% [38],in China, with a prevalence of 1.6% [39],and Wolaita, with a prevalence of 3.4% [40]. The possible reasons for the discrepancies might explain the higher prevalence in this study, may be linked to the small sample size of the studies in Wolaita; the nding from Australia was based on a prospective cohort study design;…”
Section: Discussioncontrasting
confidence: 65%